Taxonomy and biogeography of Molgolaimus Ditlevsen, 1921 (Nematoda: Chromadoria) with reference to the origins of deep sea nematodes - Fonseca, G.; Vanreusel, A.; Decraemer, W. (Antarctic Science, 2006)
Molgolaimus is a genus of free-living marine nematodes which is found in high densities (10–35% of the total community) up to 2000 m depth. Its occurrence is often associated with organically enriched and recently disturbed areas. Currently, only 16 species have been described, mainly from shallow waters. The present study contributes 17 new species mainly from the Weddell Sea but also from the Pacific Ocean, and provides an illustrated polytomous identification key to species level. The 33 Molgolaimus species described can be identified based on just a few morphometric features: spicule length, body length, anal body diameter, tail length and pharynx length. A first insight into the biogeography of this deep sea genus at species level is presented. A comparison of morphometric characteristics between species suggests that the most similar species co-occur in the same geographical region, rather than within the same bathymetric zones or similar ecosystems separated over long distances. These observations suggest that deep sea nematodes may not have a common origin but might have derived “recently” from shallow water taxa. Therefore, global distribution of nematodes could be explained by means of palaeogeographical events.
NeMys doc_id: 16476